The deterrent effects of prison: evidence from a natural experiment - Francesco Drago; Roberto Galbiati; Pietro Vertova (Institute for the Study of Labor (IZA), 2007)
In this paper we test for the theory of deterrence. We exploit the natural experiment provided by the Collective Clemency Bill passed by the Italian Parliament in July 2006. As a consequence of the provisions of the bill, expected punishment to former inmates recommitting a crime can be considered as good as randomly assigned. Based on a unique data set on post-release behaviour of former inmates, we find that an additional month in expected sentence reduces the propensity to recommit a crime by 1.24 percent: this corroborates the general deterrence hypothesis. However, this effect depends on the time previously served in prison: the behavioural response to an additional month of expected sentence decreases with the length of the prison spell. This second result can be hardly reconciled with the specific deterrence hypothesis according to which a stronger past experience of punishment should increase the sensitivity to future expected sanctions.
Keywords: 330; Kriminalität; Strafvollzug; Dauer; Kriminalitätsökonomik; Test; Italien